FAKTOR EKSTERNAL PENGHAMBAT PENCAPAIAN STANDAR KECAKAPAN BAHASA INGGRIS PADA MAHASISWA PARIWISATA BERDASARKAN COMMON ASEAN TOURISM CURRICULUM - Ni Nyoman Yunike Kurniarini (JAPAM (Jurnal Pendidikan Agama), 2024)
This study is aimed to investigate external factors that hinder the students' attainment of English proficiency in the Common ASEAN Tourism Curriculum. The study was conducted on tourism students in AKN Lombok Barat. The study used a descriptive qualitative method and the data was gained through competency-based assessment and questionnaire for the students in three subdivisions; Hotel Accommodation, Food Beverages, and Hotel Engineering. The findings showed that several factors hinder the students' achievement of English proficiency standards externally. The external factors comprise the unsupportive college cultural factors; the dominant use of the mother tongue; the lack of English facilities in the college, such as an English listening laboratory to support the learning process; the limited learning hours for English subjects: the lecturers have limited interaction in English, especially outside the classroom; the lecturer has limited strategies in their teaching method, especially in practicing English for specific purposes like in tourism